Kompetensi Guru Dalam Memanfaatkan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi (TIK) di SMA Putra Bangsa Depok - Amalia, Rini; Sagita, Sri Melati; Faisal, Ahmad (Yayasan Daarul Huda Kruengmane, 2024)
The use of information technology due to advances in science and technology has an impact on global changes in educational institutions. This change has a major influence on the use of information technology in improving teacher competence in schools. Teachers are expected to start improving their knowledge and skills to be more creative in utilizing learning media based on information and communication technology optimally, so that it can be used as widely as possible for the progress of the nation's children and to achieve school excellence. There are many things that can be done to improve competence. One thing that can be done is to utilize the Bandicam and Google Form applications in learning media in schools.